[Andrásovits 5]
travelling with emigrants on the Danube to the Black See, starting from Budapest, people on the ship everywhere & every position, book in Hebrew, praying, from the ship the Danube and theshore with rocks, Russe, harbour, the town, people, wedding on the ship, Braila, Galatz